Energy‐dispersive X‐ray micro Laue diffraction on a bent gold nanowire. Issue 1 (17th December 2020) - AlHassan, Ali; Abboud, A.; Cornelius, T. W.; Ren, Z.; Thomas, O.; Richter, G.; Micha, J.-S.; Send, S.; Hartmann, R.; Strüder, L.; Pietsch, U.
Abstract : This article reports on energy‐dispersive micro Laue (µLaue) diffraction of an individual gold nanowire that was mechanically deformed in three‐point bending geometry using an atomic force microscope. The nanowire deformation was investigated by scanning the focused polychromatic X‐ray beam along the nanowire and recording µLaue diffraction patterns using an energy‐sensitive pnCCD detector that permits measurement of the angular positions of the Laue spots and the energies of the diffracted X‐rays simultaneously. Abstract : This article reports on energy‐dispersive micro Laue (µLaue) diffraction of an individual gold nanowire that was mechanically deformed in three‐point bending geometry using an atomic force microscope. The nanowire deformation was investigated by scanning the focused polychromatic X‐ray beam along the nanowire and recording µLaue diffraction patterns using an energy‐sensitive pnCCD detector that permits measurement of the angular positions of the Laue spots and the energies of the diffracted X‐rays simultaneously. The plastic deformation of the nanowire was shown by a bending of up to 3.0 ± 0.1°, a torsion of up to 0.3 ± 0.1° and a maximum deformation depth of 80 ± 5 nm close to the position where the mechanical load was applied. In addition, extended Laue spots in the vicinity of one of the clamping points indicated the storage of geometrically necessary dislocations with a density of 7.5 × 10 13  m −2 . While µLaue diffraction with a non‐energy‐sensitive detector only gives access to the deviatoric strain, the energy sensitivity of the employed pnCCD offers absolute strain measurements with a resolution of 1%. Here, the residual strain after complete unloading of the nanowire amounted to maximum tensile and compressive strains of the order of +1.2 and −3%, which is comparable to the actual resolution limit. The combination of white‐beam µLaue diffraction using an energy‐sensitive pixel detector with nano‐mechanical testing opens up new possibilities for the study of mechanical behavior at the nanoscale.